2016
DOI: 10.5114/pjp.2016.63770
|View full text |Cite
|
Sign up to set email alerts
|

Are mast cells important in diabetes?

Abstract: Diabetes is a metabolic disorder characterized by hyperglycemia and associated with microvascular and macrovascular syndromes mediated by mast cells. Mast cells are activated through cross-linking of their surface high affinity receptors for IgE (FcεRI) or other antigens, leading to degranulation and release of stored inflammatory mediators, and cytokines/chemokines without degranulation. Mast cells are implicated in innate and acquired immunity, inflammation and metabolic disorders such as diabetes. Histamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“… noted that adipose tissue‐conditioned medium from the non‐obese stages of db/db mice increased the migration of bone marrow‐derived mast cells (BMMCs). It is suggested that immature mast cells that infiltrate into adipose tissue at the non‐obese stage progressively mature and contribute to the obesity and diabetes progression .…”
Section: Adipose Tissue As a Reservoir Of Mast Cellsmentioning
confidence: 99%
“… noted that adipose tissue‐conditioned medium from the non‐obese stages of db/db mice increased the migration of bone marrow‐derived mast cells (BMMCs). It is suggested that immature mast cells that infiltrate into adipose tissue at the non‐obese stage progressively mature and contribute to the obesity and diabetes progression .…”
Section: Adipose Tissue As a Reservoir Of Mast Cellsmentioning
confidence: 99%
“…The levels of insulin in the extracellular milieu are of relevance to mast cells and basophils, and in turn, the functionality of these cells is of relevance to outcomes in metabolic disorders [ 5 7 ]. Mast cells and basophils bear the insulin receptor, and are regulated by insulin levels.…”
Section: Introductionmentioning
confidence: 99%
“…Activated mast cells owe their fundamental role in inflammation to the production and release of a wide range of inflammatory as well as non-inflammatory mediators. These may be classified into three groups: preformed mediators, which are stored in the granules and secreted during degranulation almost instantaneously after mast cell activation; mediators de novo synthesised during membrane phospholipid metabo-lism, which are produced and released in tens of minutes after activation; and newly synthesised cytokines and other mediators, which are formed and secreted several hours after mast cell activation (Table I) [24,25,26,27,39,40,41,42].…”
Section: Mast Cellsmentioning
confidence: 99%